THE PRESERVATION OF HIGH-PRESSURE ROCKS DURING EXHUMATION: METAGRANITES AND METAPELITES - Proyer A. (My University, 2003)
Metagranites in the NKFMASH system require external hydration during prograde high-pressure metamorphism in order to equilibrate to ambient HP conditions by producing more siliceous muscovite. Any lack of external fluid or the disappearance of biotite stops re-equilibration and thus prevents recording of high-pressure conditions. The same hydration reactions cause dehydration during exhumation. Orthogneiss from shear zones or adjacent to metapelites and metabasites will take up external fluid during subduction and record the highest P-T conditions, but will also be the first to dehydrate upon exhumation, now hydrating other lithologies and probably refuelling shearzones.The (de)hydration behavior of Ca-bearing metagranitoids is similar to that in the Ca-free system. However, the anorthite component of plagioclase decomposes with increasing pressure to form either (clino)zoisite or a grossular-rich garnet. Both reactions are fluid-consuming. If H2O is supplied from an external source, the garnet-bearing assemblage can record P-T conditions up to very high pressures, but dehydrates again during heating and/or decompression to form a more Fe-rich garnet and Al-rich mica(s). The garnet compositions observed in natural HP-metagranites are mostly too Fe-rich to be formed in the presence of an H2O-rich fluid.N(C)KFMASH metapelites generally have a more complex mineralogy and succession of mineral assemblages along a P-T path. The H2O contained in hydrous silicates like chlorite and chloritoid is only partly released, but partly transferred to other minerals like paragonite, glaucophane or phengite during subduction and further dehydration during exhumation is common. The mineral assemblage preserved by the rock may then record P-T conditions way below those of the actual pressure and temperature peak of the path. Contouring of the P-T pseudosection of a specific metapelite composition with mode isopleths for H2O shows which P-T conditions along a given path are the ones most likely recorded by the rock.
Keywords: METAGRANITE; METAPELITE; PRESERVATION; HIGH PRESSURE